THE POLITICS OF EDUCATION OF NIZAM AL-MULK: A Socio-Political Study of the Nizhamiyah Madrasahs - Kurniawan, Muhammad Rafiq Kurniawan (Tsaqofah : Jurnal Pendidikan Islam, 2022)
Islamic educational institutions have always developed in line with the needs and changes of society. The development of society is characterized by the progress of science and the need to preach Islam. The 5th century Hijriyah, at the time of the establishment of madrassas, the scientific development of the community, especially Muslims, can be said to have reached a perfect stage, because almost all sciences both al-ulum an-naqliyah and al-ulum al-aqliyah have been compiled and systematized. Such conditions should be reflected in the education efforts of the people. However, due to the political interests of the government which makes education a means to achieve its goals, the subject matter in madrasas is very loaded with political content or sectarian goals. The ideologization of subject matter in madrassas also impacts on learning methods that tend to be closed and indoctrinating, thus not providing space for the development of a critical and free way of thinking. Using a socio-political approach, this study tries to trace the birth of the Nizhamiyah madrasa which was based on multiple motivations. With its Shafi'i-minded board of teachers, the Nizhamiyah madrasa is seen as a manifestation of the triumph of the theological-dogmatic movement that joins the Sunni madrasa to counterbalance the dominance of the Mu'tazilah-Hambali and the dominance of Shi'ah. So that the subjects of study pursued are characterized by Asy'ariyah and fiqh-oriented understanding. The realm of "intellectualism" was lost in the educational process of this madrasa. However, Nizhamiyah is still understood as the most important Islamic educational institution and a model in the study of the social history of Islamic education. Keywords: Politics of Education, Nizam al-Mulk, and Nizhamiyah Madrasah.